Answer:
4/663
Step-by-step explanation:
There are 4 queens and 4 kings in a deck. Drawing a queen would be 4/52. Drawing a king afterwards with replacing the queen would be 4/51 because you took a queen but didn't replace that one queen card so the deck has only 51 cards left after you drew the queen. Drawing a queen would not affect your chance of drawing a king card, it will only affect the total number of cards left because you didn't replace the card afterwards. 4*4=16;52*51=2652. 16/2652 can be simplified to 4/663 by dividing 4 to both numbers. 16/4=4 and 2652/4=663. The probability of drawing a queen then a king without replacement would be 4/663.
Answer:
2/16
Step-by-step explanation:
The answer is 2/16
brainliest?
Probabilities are used to determine the likelihood of events
The value of the probability P(thinking of a song)P(turn on the radio and hear the song) is 0.056
<h3>How to estimate the probability</h3>
To calculate the probability, we make use of the following representations:
- Event A represents the likelihood of thinking of a song
- Event B represents the likelihood of turning on the radio and hearing the song
So, we have:
P(thinking of a song)P(turn on the radio and hear the song) = P(A) * P(B)
Assume that:
P(A) = 0.12 and P(B) = 0.47
So, we have:
P(thinking of a song)P(turn on the radio and hear the song) = 0.12* 0.47
Evaluate the product
P(thinking of a song)P(turn on the radio and hear the song) = 0.0564
Approximate
P(thinking of a song)P(turn on the radio and hear the song) = 0.056
Hence, the value of the probability P(thinking of a song)P(turn on the radio and hear the song) is 0.056
Read more about probabilities at:
brainly.com/question/25870256
Answer:
x = 10.3 in
Step-by-step explanation:
To find the value of a, use the area formula for a triangle. The formula is A = 1/2 *b*h. Here b = x and h= x. The formula becomes A = 1/2 *x². Substitute A = 53 and solve for x by using inverse operations.
A = 1/2x²
53 = 1/2x²
106 = x²
√106 = x
10.3 = x
Answer:
4x^2 + 12x + 9.
Step-by-step explanation:
(2x+3)^2
= (2x+3)(2x+3)
= 2x(2x+3)+3(2x+3)
= 4x^2 + 6x + 6x + 9
= 4x^2 + 12x + 9.